2016
DOI: 10.1016/j.jsams.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of US adult physical activity and sedentary behavior patterns

Abstract: Objectives Physical activity and sedentary behavior patterns may be differentially associated with socio-demographic and health measures. We explored correlates of day-to-day patterns over a week in accelerometer measured physical activity and sedentary behavior to inform intervention development. Design Cross-sectional study Methods National Health and Nutrition Examination Survey (NHANES) adult participants (≥20 years) in 2003–2006 wore an accelerometer for 1 week. Accelerometer data from 7236 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 30 publications
(54 reference statements)
6
51
1
Order By: Relevance
“…The authors reported strong evidence for positive associations between physical activity and intrapersonal factors of health status, self‐efficacy, male gender, and education level, as well as negative associations between physical activity and body mass index (BMI) and age. Similar findings were reported by Rai et al () and Jones, Wen, Herring, and Evenson (). At the interpersonal level, social support has been positively associated with physical activity (Bauman et al, ; Smith, Banting, Eime, O’Sullivan, & van Uffelen, ; Thornton et al, ).…”
Section: Introductionsupporting
confidence: 91%
“…The authors reported strong evidence for positive associations between physical activity and intrapersonal factors of health status, self‐efficacy, male gender, and education level, as well as negative associations between physical activity and body mass index (BMI) and age. Similar findings were reported by Rai et al () and Jones, Wen, Herring, and Evenson (). At the interpersonal level, social support has been positively associated with physical activity (Bauman et al, ; Smith, Banting, Eime, O’Sullivan, & van Uffelen, ; Thornton et al, ).…”
Section: Introductionsupporting
confidence: 91%
“…Older age, female sex, history of chronic disease, and higher BMI were consistently associated with lower odds, and having better self-rated health and being employed were consistently associated with higher odds of being assigned into a more active compared with a less active class. 5 …”
Section: Discussionmentioning
confidence: 99%
“…This class was more likely to be older, have a higher education, need special equipment to walk, and have at least one of several health conditions (e.g., morbid obesity, diabetes, cardiovascular disease, cancer, emphysema). 5 Although deaths in the first 2 years of follow-up were excluded, reverse causality may still occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown among nationally representative adult samples from 32 European countries, occupational SB may explain lower odds of being in less sedentary latent classes . Occupational and leisure‐time SB may have different health effects due to different patterns of sitting accumulation (eg, duration and repetitiveness) or the context in which SB occurs . Furthermore, recent studies have found that leisure‐time SB had stronger effects on cardiorespiratory and cardiometabolic health compared to occupational SB .…”
Section: Discussionmentioning
confidence: 98%